CompTIA security+ certification study guide (exam SY0-401) - Clarke, Glen E. (McGraw-Hill, 2014)
With hundreds of practice exam questions, including new performance-based questions, this second edition covers what you need to know--and shows you how to prepare--for this challenging exam. It has 100% complete coverage of all official objectives for exam SY0-401; Exam Watch notes call attention to information about, and potential pitfalls in, the exam; inside the exam sections in every chapter highlight key exam topics covered; two-minute drills for quick review at the end of every chapter; simulated exam questions--including performance-based questions--match the format, topics, and difficulty of the real exam. --